2020
DOI: 10.29103/ijevs.v2i9.2694
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Blended Learning Model on Motivation and Students’ Learning Achievement

Abstract: This study aims to determine differences in student motivation and learning achievement in KKPI subjects between students who use the face-to-face learning model and students who use blended learning models, increased motivation and student achievement in KKPI subjects due to the application of the blended model learning, and the interaction of the influence of the application of learning models and motivation on KKPI student learning achievement at SMK 1 Kamal Bangkalan. This quasi-experimental study uses two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This model emphasizes the right mix of online and face-to-face learning to enhance the learning experience. Additionally, studies have highlighted the positive impact of blended learning on student motivation and learning achievement (Rahman et al, 2020).…”
Section: Blended Learning Approaches and Modelsmentioning
confidence: 99%
“…This model emphasizes the right mix of online and face-to-face learning to enhance the learning experience. Additionally, studies have highlighted the positive impact of blended learning on student motivation and learning achievement (Rahman et al, 2020).…”
Section: Blended Learning Approaches and Modelsmentioning
confidence: 99%
“…This finding is consistent with Haryadi & Fitria (2021), who reported that students found it difficult to understand the content of the materials presented in online learning. Students' lack of learning motivation during learning online also emerged as another problem, which could be caused by the lack of familiarity of students with online learning and limited facilities for online learning (Rahman, 2020).…”
Section: Students' Perceived Problems In Online Learningmentioning
confidence: 99%
“…The use of different methods causes different learning effectiveness [9]. A blended learning model can improve student motivation and learning achievement [10,11]. From another perspective regarding online learning, several research results also show different results.…”
Section: The Effect Of a Blended Learning Model On Students' Learning Process And Outcomementioning
confidence: 99%